The Effect of Psycho-educational Intervention on the Caregiver burden among Caregivers of Hemodialysis Patients - Masumeh Hemmati Maslakpak; Mehdi Torabi; Moloud Radfar; Vahid Alinejad (Golestan University of Medical Sciences, 2019)
Background and objectives: Chronic renal failure has a progressive nature and there is always a need for a person to care for them. A caregiver, who is usually a patient's family member, may face many problems during the care process, which ultimately causes burnout. The aim of this study is to determine the effect of psycho-educational intervention on the caregiver burden of patients undergoing hemodialysis. Methods: This study was a clinical trial that carry out on 105 caregivers of patients undergoing hemodialysis. The burnout questionnaire of Zarit was completed by the participants. The Caregivers were allocated randomly in two groups of intervention (discussion, workshops) and control. Two weeks after the completion of 6 sessions of the group discussion and 4 sessions of the workshop, caregiver burdon questionnaire of Zarit was completed again. Data was analyzed by using version 16 of spss software and parametric and non-parametric tests. Results: Results showed that there was no significant difference between the three groups before intervention in the mean scores of burden (p=0.423). However, after the intervention there was significant difference in the mean scores of burden between intervention groups with control group (p<0.001). Tukey post hoc test showed no significant difference between the two intervention groups in the mean scores of burden (P=0.204). Conclusion: The results of this study can be found that training classes such as group discussion had a significant reduction in the severity of caregiver burden. Therefore, it is recommended that in the health system planning attend to the role of family members in the treatment of these patients also benefit from this training method.